Перспективи вдосконалення кола обов’язків, які покладаються на особу, звільнену від відбування покарання з випробуванням - Фідря, Ю.; Fidria, Iu. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано окремі проблемні питання, що стосуються закріпленого у ст. 76 КК України кола обов’язків, які суд може покласти на особу, звільнену від відбування покарання з випробуванням. Досліджено правову природу таких обов’язків, з’ясовано їх значення для досягнення цілей випробування, а також критерії, якими керується суд при їх призначенні. Сформульовано ряд пропозицій щодо вдосконалення кримінального законодавства, яке передбачає перелік обов’язків, які можуть бути покладені на особу, звільнену від відбування покарання з випробуванням. Внесено пропозицію доповнити законодавчий перелік вказівкою на обов’язок відшкодування шкоди, заподіяної злочином. The article analyzes some problematic issues concerning fixed in Art. 76 of the Criminal Code of Ukraine range of duties which the court may impose on the persons released from probation. In the focus of attention is the legal nature of court-appointed duties, their importance for achieving the objectives of probation and the criteria governing their appointment at court. The author suggests the classification of duties on the basis of identity (general and specific) and the functional purpose (social, resocialization, checking (prevention and rehabilitation); legislative proposal to supplement the list indicating the duty of compensation for harm caused by the crime that will provide the restoration of social justice and effective legal protection of rights and legal interests of the victim. The article clarifies some items of the Law of Ukraine «On probation» relating to the establishment of supervisory kind of probation to the persons released from probation, and implementation of programs on their approbation. The author gives the arguments for expansion of the list of legislative duties that the court may impose on persons released on probation, and securing the right of the court to impose others, not provided by the law on criminal responsibility duties, but taking into account the whole complex of factors, circumstances and conditions concerning the convicted and the crime committed by him.
Prospects for Improving the Range of Duties Imposed on the Persons Released from Probation.
Keywords: звільнення від відбування покарання; пробація; випробування; іспитовий строк; виправлення; release from serving the sentence; probation; trial; chastisement